Ruptured sinus of Valsalva aneurysm coexisted with congenital ventricular septal defect: a case series - Ni Made Ayu Wulan Sari; Made Satria Yudha Dewangga; Ida Bagus Rangga Wibhuti; Luh Oliva Saraswati Suastika; I Dewa Gede Surya Mahardika Badung; Bryan Gervais de Liyis; Anastasya Maria Kosasih; Gusti Ngurah Prana Jagannatha (The Egyptian Heart Journal, 2023)
Abstract Background Ruptured sinus of Valsalva aneurysm (RSoVA) is an uncommon cardiac anomaly that may occasionally coexist with additional congenital heart disease (CHD). The presence of such congenital cardiac anomalies, frequently involving a ventricular septal defect (VSD), is of significant clinical importance and warrants vigilant detection during echocardiographic assessments to prevent oversight. Case presentation Three cases of RSoVA accompanied by VSD are presented in which all patients manifested symptoms of shortness of breath (SOB). In the first patient, right and left heart catheterization was undertaken; however, the images failed to reveal any evidence of VSD flow due to the occlusion of a small VSD by the prolapsed right coronary cusp (RCC). Prior to surgical intervention, multimodal imaging was conducted, revealing the presence of RSoVA extending into the right ventricle (RV) along with the VSD. The second patient had a prior childhood diagnosis of VSD but had not undergone further medical intervention. Transoesophageal echocardiography (TEE) was subsequently performed, identifying the presence of RSoVA, a small VSD, and valvular heart disease. The third patient presented with heart failure, exacerbated during her second pregnancy. TEE was also administered to this patient, revealing the presence of RSoVA accompanied by a small subaortic VSD with a left-to-right shunt. All three patients were scheduled for surgical repair of the ruptured sinus of Valsalva and closure of the VSD. Conclusions The coexistence of RSoVA and CHD, typically VSD, is frequently observed in patients experiencing symptoms of SOB. Recognizing the presence of CHD in individuals with RSoVA is of paramount importance, as it can significantly influence their medical management and treatment strategies.